Evaluation of an eHealth Intervention in Chronic Care for Frail Older People: Why Adherence is the First Target - Makai, Peter; Perry, Marieke; Robben, Sarah HM; Schers, Henk J; Heinen, Maud M; Olde Rikkert, Marcel GM; Melis, René F (JMIR Publications, 2014)
BackgroundOlder people suffering from frailty often receive fragmented chronic care from multiple professionals. According to the literature, there is an urgent need for coordination of care. ObjectiveThe objective of this study was to investigate the effectiveness of an online health community (OHC) intervention for older people with frailty aimed at facilitating multidisciplinary communication. MethodsThe design was a controlled before-after study with 12 months follow-up in 11 family practices in the eastern part of the Netherlands. Participants consisted of frail older people living in the community requiring multidisciplinary (long-term) care. The intervention used was the health and welfare portal (ZWIP): an OHC for frail elderly patients, their informal caregivers and professionals. ZWIP contains a secure messaging system supplemented by a shared electronic health record. Primary outcomes were scores on the Instrumental Activities of Daily Living scale (IADL), mental health, and social activity limitations. ResultsThere were 290 patients in the intervention group and 392 in the control group. Of these, 76/290 (26.2%) in the intervention group actively used ZWIP. After 12 months follow-up, we observed no significant improvement on primary patient outcomes. ADL improved in the intervention group with a standardized score of 0.21 (P=.27); IADL improved with 0.50 points, P=.64. ConclusionsOnly a small percentage of frail elderly people in the study intensively used ZWIP, our newly developed and innovative eHealth tool. The use of this OHC did not significantly improve patient outcomes. This was most likely due to the limited use of the OHC, and a relatively short follow-up time. Increasing actual use of eHealth intervention seems a precondition for large-scale evaluation, and earlier adoption before frailty develops may improve later use and effectiveness of ZWIP.